Planning and forecasting demand for aircraft engines airline fleet - Кучер, А.Г.; Мустафа, Мустафа А.С. (Proceedings of National Aviation University (archive), 2007)
The questions of air-engines supply system processes analysis on the basis of order planning and air-engine demand forecasting of airline’s air fleet with the use of imitating simulation methods are considered.